Perancangan Prototipe Sistem Informasi Pengadaan Barang Berbasis Website pada Divisi Logistik dengan Metode Waterfall - Ni Made Nola; Ni Made Cyntia Utami; Aisya B Diji; I Gusti Ngurah Priambadi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Purchase of foods is crucial activity in ensuring the smooth operation of company, particularly within the Purchase Unit of the Logistics Division at PT Z. The manual process of submitting purchase status information, triggered by frequent daily information request, leads to work duplication and communication inefficiencies. This study aims to design a prototype od web-bases purchase information system capable of presenting real-time and structures data. The system was developed using Waterfall method, encompassing stages of requirement analysis, system design using UML diagram (use case and activity diagram), interface implementation using Figma, and testing via the Black Box method. The resulting design consists of several key modules, including Dashboard, Monitoring progress, Monitoring Budget, Checksheet, List Vendor. The results indicate that the system performs according to user requirements. This prototype is expected to enhance communication efficiency and support transparent information delivery in the purchase process within the Logistics Division at PT Z.